2006
DOI: 10.5049/ebp.2006.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthesis in the Adult and Developing Kidney

Abstract: Nitric oxide (NO) is synthesized within the adult and developing kidney and plays a critical role in the regulation of renal hemodynamics and tubule function. In the adult kidney, the regulation of NO synthesis is very cell type specific and subject to distinct control mechanisms of NO synthase (NOS) isoforms. Endothelial NOS (eNOS) is expressed in the endothelial cells of glomeruli, peritubular capillaries, and vascular bundles. Neuronal NOS (nNOS) is expressed in the tubular epithelial cells of the macula de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The abundance of the substrate, L-arginine, is well-maintained during aging, but there are increases in the concentration of circulating endogenous NOS inhibitors, which could contribute to a powerful inhibitory effect in adult normotensive animals and weakened in young animals [44]. In the renal cortex of normotensive rats, both endothelial and neuronal NOS [45] are abundantly expressed. All three isoforms of NOS (nNOS, iNOS, and eNOS) could have a higher expression of the mRNA or protein level in SHR compared to Wistar Kyoto rats [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of the substrate, L-arginine, is well-maintained during aging, but there are increases in the concentration of circulating endogenous NOS inhibitors, which could contribute to a powerful inhibitory effect in adult normotensive animals and weakened in young animals [44]. In the renal cortex of normotensive rats, both endothelial and neuronal NOS [45] are abundantly expressed. All three isoforms of NOS (nNOS, iNOS, and eNOS) could have a higher expression of the mRNA or protein level in SHR compared to Wistar Kyoto rats [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present study indicated that iNOS is widely expressed in renal tubule epithelia, including the proximal, distal and collecting tubules. iNOS is known to play significant roles in the regulation of kidney hemodynamics (Han, Jung, Chung, Kim, & Kim, 2006). Wang (2002) has confirmed that iNOS regulates tubular water and electrolytes excretion in the kidney and the tubular reabsorptive function as well as, it has a role in the regulation of renal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression was also found in the epithelia of TAL of Henle and CD (180). Whereas nNOS was detected predominantly in the tubular epithelial cells of the macula densa (114) in the kidneys of rat, mouse, guinea pig, and rabbit, the intensity of signal was much weaker in humans and pigs (18). Additionally, nNOS was also detected in inner and outer medullary CD, efferent arterioles, Bowman's capsule, and various cells at the cortical TAL in rats (311).…”
Section: Endothelium-associatedmentioning
confidence: 91%
“…Interestingly, expression of all three isoforms have been detected in the kidney tissues but have different distribution profiles (168). For example, eNOS was found to be expressed in the endothelial cells (ECs) of glomeruli and peritubular capillaries in the cortex, and in the ECs of vascular bundles in the medulla, with a stronger immunoreactivity in the cells of renal medulla than in the cortex (114). Its expression was also found in the epithelia of TAL of Henle and CD (180).…”
Section: Endothelium-associatedmentioning
confidence: 99%